1986
DOI: 10.1128/aac.29.1.77
|View full text |Cite
|
Sign up to set email alerts
|

Activities of 1-(2-deoxy-2-fluoro-beta-D-arabinofuranosyl)-5-iodocytosine and its metabolites against herpes simplex virus types 1 and 2 in cell culture and in mice infected intracerebrally with herpes simplex virus type 2

Abstract: As measured by plaque and yield reduction assays, several metabolites of 1-(2-deoxy-2-fluoro-,B-Darabinofuranosyl)-5-iodocytosine (FIAC) were highly active against herpes simplex virus types 1 and 2. These metabolites included the 2'-deoxy-2'-fluoroarabinosyl derivatives of 5-iodouracil (FIAU), cytosine (FAC), uracil (FAU), and thymine (FMAU). In mice inoculated intracerebrally with herpes simplex virus type 2, the relative order of potency of these compounds and licensed antiviral drugs was as follows: FMAU»>… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
15
0

Year Published

1986
1986
2001
2001

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 35 publications
(16 citation statements)
references
References 25 publications
(35 reference statements)
1
15
0
Order By: Relevance
“…This result compared favorably with those of earlier studies, in which the ED50s were 2.8 ,uM for FMAU and >200 ,uM for FEAU (7,11,12). The ED50s of FEAU against HSV-1 and HSV-2 were 0.024 and 0.24 ,uM, respectively.…”
Section: Resultssupporting
confidence: 79%
“…This result compared favorably with those of earlier studies, in which the ED50s were 2.8 ,uM for FMAU and >200 ,uM for FEAU (7,11,12). The ED50s of FEAU against HSV-1 and HSV-2 were 0.024 and 0.24 ,uM, respectively.…”
Section: Resultssupporting
confidence: 79%
“…In contrast, 3TC-treated cells did not induce any apparent morphological changes under the same conditions (data not shown). of herpes simplex virus and cytomegalovirus infections (18,29) was recently reported to be also effective against HBV replication (3,4). The anti-HBV activity of the 5 '-triphosphate form of FIAU is assumed to result from its selective inhibition of viral targets, possibly HBV DNA polymerase (30).…”
Section: Resultsmentioning
confidence: 99%
“…The human hepatoma HepG2 cell line isolated by Aden et al (12) and the 2.2.15 cell line which consists of HepG2 cells transfected with HBV (13) were selected for these investigations since the HepG2 cell line retains many characteristics of hepatocytes, is an adequate in vitro model in which to examine liver functions (14,15), and can be transfected with HBV leading to production of infectious virions (13). Only scant data have been reported on the in vitro and in vivo metabolism of FIAU but more extensive investigations have been carried out with FIAC, a nucleoside extensively deaminated in vivo to FIAU (16)(17)(18). From these studies, it is clear that several metabolites of FIAU can be formed including FAU, FMAU, FHMAU and glucuronides of FIAU and FMAU (16)(17)(18).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…We have studied several licensed and experimental drugs which could be candidates for this purpose. Based on animal studies with ara-A, ACV, several 2'-fluoroarabinosyl pyrimidine nucleosides, including 2'-fluoro-5-methylarabinosyluracil (FMAU) and 2'-fluoro-5-iodoarabinosylcytosine (FIAC) (10,20,22), and congeners of acyclovir, such as 9-[(2,3-dihydroxypropoxy)methyl]guanine (DHPG; also known as 2'-NDG, BIOLF-62, and BW759) (27) and buciclovir (9; unpublished data), we concluded that FMAU was the best candidate to be evaluated in humans with severe herpetic infection (20).…”
mentioning
confidence: 99%